Lava dome morphology inferred from numerical modelling. Issue 3 (21st August 2020) - Tsepelev, Igor; Ismail-Zadeh, Alik; Melnik, Oleg
SUMMARY: Lava domes form when highly viscous magmas erupt on the surface. Several types of lava dome morphology can be distinguished depending on the flow rate and the rheology of magma. Here, we develop a 2-D axisymmetric model of magma extrusion on the surface and lava dome evolution and analyse the dome morphology using a finite-volume method implemented in Ansys Fluent software. The magma/lava viscosity depends on the volume fraction of crystals and temperature. We show that the morphology of domes is influenced by two parameters: the characteristic time of crystal content growth (CCGT) and the discharge rate (DR). At smaller values of the CCGTs, that is, at rapid lava crystallization, obelisk-shaped structures develop at low DRs and pancake-shaped structures at high DRs; at longer CCGTs, lava domes feature lobe- to pancake-shaped structures. A thick carapace of about 70 per cent crystal content evolves at smaller CCGTs. We demonstrate that cooling does not play the essential role during a lava dome emplacement, because the thermal thickness of the evolving carapace remains small in comparison with the dome's height. A transition from the endogenic to exogenic regime of the lava dome growth occurs after a rapid increase in the DR. A strain-rate-dependent lava viscosity leads to a more confined dome, but the influence of this viscosity on the dome morphology is not well pronounced. The model results can be used in assessments of the rates of magma extrusion, the lava viscosity and the morphology of active lava domes..